2011
DOI: 10.1002/cjoc.201100273
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3‐ and GaCl3‐Catalyzed Dehydrative Coupling Reaction of Chromone‐Derived Morita‐Baylis‐Hillman Alcohols with Terminal Alkynes

Abstract: FeCl 3 -and GaCl 3 -catalyzed dehydrative coupling reactions of chromone-derived Morita-Baylis-Hillman (MBH) alcohols with terminal alkynes were developed. The reactions provided exclusively α-regioselective and acetylene-substituted products in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Only a highly regioselective coupled product 20 was observed, without other regioisomer 21 as well as hydration products i. e. ketone 22 from the corresponding vinyl carbocation 23". [10] Interestingly, other Lewis acids such as Sc(OTf) 3 and AgOTf provided the product 20 in traces whereas no reaction occurred with FeCl 2 , Fe(OTf) 2 and Fe(acac) 3 .…”
Section: Dehydrative Couplingsmentioning
confidence: 99%
“…Only a highly regioselective coupled product 20 was observed, without other regioisomer 21 as well as hydration products i. e. ketone 22 from the corresponding vinyl carbocation 23". [10] Interestingly, other Lewis acids such as Sc(OTf) 3 and AgOTf provided the product 20 in traces whereas no reaction occurred with FeCl 2 , Fe(OTf) 2 and Fe(acac) 3 .…”
Section: Dehydrative Couplingsmentioning
confidence: 99%
“…50 Liu et al reported a GaCl 3 -catalysed dehydrative coupling reaction of chromone-derived Morita-Baylis-Hillman alcohols with terminal alkynes (Scheme 22). 51 These reactions were exclusively a-regioselective and furnished alkyne-substituted products in good The dihydropyrimidinone motif appears in many pharmacologically active compounds including calcium channel modulators, a 1a -antagonists, anticancer drugs, and anti-HIV marine natural products. 52 Jianping et al have described a novel route to dihydropyrimidine-2(1H)-ones using gallium catalysis.…”
Section: Coupling Reactionsmentioning
confidence: 99%
“…Previous reports on the direct coupling of alcohols with alkynes have employed Lewis acids such as, Fe(OTf) 3 /TfOH [14] and FeBr 2 , [15] Cu(OTf) 2 , [16] as well as FeCl 3 or GaCl 3 [17] . Additionally, Lewis acid‐catalyzed alkynylation between alkynylboron dihalides and alkoxides was achieved [18] and the direct substitution of hydroxyl groups with alkynyltrimethylsilanes was also reported using InCl 3 , [19] BiCl 3 , [20] and InCl 3 ‐Me 3 SiBr [21] …”
Section: Introductionmentioning
confidence: 99%